O novo poder normativo do TST : dissídios individuais e atores coletivos - Artur, Karen (Universidade Federal de São Carlos, 2009)
This research aims to analyze the institutional changes in labor law and in the Labor Justice courts after the Constitution of 1988. It focuses on the uniform decisions of the Superior Labor Court (TST), as well as the political dynamic between this court and the other powers and actors invested in the institution. We carried out a study of the jurisprudence of the court in individual conflicts, and conducted interviews with relevant actors to achieve this goal. Those interviewed include ministers of the TST, judges of the Labor Judges National Association, lawyers of the judicial advisory boards of the main national trade union centers, and law firms representing businesses and financial corporations. We concluded that the Labor Judiciary Power has been the leader in reforms of the institution itself, in addition to labor law in Brazil, and that it has conferred asymmetric powers to social actors in this process. Moreover, we indicate the limits of this leadership in our legislative model of labor relations.
Keywords: Ciência política; Brasil. Tribunal Superior do Trabalho; Justiça do trabalho; Direito do trabalho; Direito e política; Mudança institucional; Superior Labor Court -TST; Labor Justice; Labor law; Law and politics; Institutional Change; CIENCIAS HUMANAS::CIENCIA POLITICA